The dependence of cylindrical resonator natural frequencies on the fluid density; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Rudachenko V. A. Vadim Aleksandrovich (Modern Oilfield Equipment and its Upgrading, 2015)
Title screen